Hubungan Komunikasi Efektif SBAR Dengan Keselamatan Pasien Dan Penatalaksanaan Lanjut Untuk Meningkatkan Pelayanan Di RSU Mitra Sejati Tahun 2025 - Ratih Widya Wati Gultom; Diah Karlina (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Effective communication is an important indicator of patient safety, and the Situation, Background, Assessment, Recommendation (SBAR) method has been proven to enhance the accuracy and efficiency of information exchange among healthcare professionals. This study aims to determine the relationship between effective SBAR communication and patient safety as well as follow-up management at RSU Mitra Sejati in 2025. This research employed a cross-sectional design with a population of all nurses (180 respondents) selected through total sampling, and data were analyzed using the chi-square test at α=0.05. The results showed that 59.4% of respondents demonstrated good SBAR communication and 58.3% complied with patient safety standards, with statistical tests indicating a significant relationship between SBAR communication and patient safety (p=0.000). These findings confirm that proper implementation of SBAR communication contributes to improving patient safety; therefore, continuous training and consistent application of SBAR are recommended to strengthen the culture of patient safety in hospitals.